Species‐specific foraging strategies and segregation mechanisms of sympatric Antarctic fulmarine petrels throughout the annual cycle. (4th April 2016) - Delord, Karine; Pinet, Patrick; Pinaud, David; Barbraud, Christophe; De Grissac, Sophie; Lewden, Agnes; Cherel, Yves; Weimerskirch, Henri
Abstract : Determining the year‐round distribution and behaviour of birds is necessary for a better understanding of their ecology and foraging strategies. Petrels form an important component of the high‐latitude seabird assemblages in terms of species and individuals. The distribution and foraging ecology of three sympatric fulmarine petrels (Southern Fulmar Fulmarus glacialoides, Cape Petrel Daption capense and Snow Petrel Pagodroma nivea ) were studied at Adélie Land, East Antarctica, by combining information from miniaturized saltwater immersion geolocators and stable isotopes from feathers. During the breeding season at a large spatial scale ( c . 200 km), the three species overlapped in their foraging areas located in the vicinity of the colonies but were segregated by their diet and trophic level, as indicated by the different chick δ 15 N values that increased in the order Cape Petrel < Southern Fulmar < Snow Petrel. During the non‐breeding season, the three fulmarines showed species‐specific migration strategies along a wide latitudinal gradient. Snow Petrels largely remained in ice‐associated Antarctic waters, Southern Fulmars targeted primarily the sub‐Antarctic zone and Cape Petrels migrated further north. Overall, birds spent less time in flight during the non‐breeding period than during the breeding season, with the highest percentage of time spent sitting on the water occurring during the breeding season and at the beginning of the non‐breeding period before migration. This activity pattern, together with the δ 13 C values of most feathers, strongly suggests that moult of the three fulmarine petrels occurred at that time in the very productive high Antarctic waters, where birds fed on a combination of crustaceans and fish. The study highlights different segregating mechanisms that allow the coexistence of closely related species, specifically, prey partitioning during the breeding season and spatial segregation at sea during the non‐breeding season.